Alterated gene expression in dilated cardiomyopathy after left ventricular assist device support by bioinformatics analysis - Wei, Ying; Cao, Hao; Peng, Yuan-Yi; Zhang, Bo (Frontiers in Cardiovascular Medicine, 2023)
Introduction Heart transplantation is the best treatment for end-stage dilated cardiomyopathy (DCM). Left ventricular assist device (LVAD) support is becoming more prevalent and may delay heart transplantation. Gene expression of the left ventricular myocardium usually changes following LVAD implantation. In this study, we aimed to identify potential biomarkers to determine the prognosis of patients with DCM after receiving LVAD support. Methods We extracted microarray datasets from Gene Expression Omnibus (GEO), including GSE430 and GSE21610. There were 28 paired DCM samples in the GSE430 and GSE21610 profiles. Differentially expressed genes (DEGs) were identified at LVAD implantation and heart transplantation. DEGs were annotated according to Gene Ontology (GO) and analyzed according to the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. A protein–protein interaction (PPI) network was constructed. The top 10 crucial genes were predicted using Cytoscape plugin CytoHubba in conformity with the network degree algorithm. The levels of gene expression and the diagnostic values of crucial genes were confirmed in the clinical datasets. Results The 28 DEGs were clustered into the GSE datasets. GO annotations and KEGG pathway enrichment analyses revealed that inflammation might be involved. They were associated with correlative inflammation. Combined with PPI networks, these results revealed CytoHubba's top 10 hub genes, including CCL2, CXCL12, CXCL1, CTGF/CCN2, CX3CR1, POSTN, FKBP5, SELE, AIF1, and BMP2. Among them, CCL2, CXCL12, FKBP5, and BMP2 might be considered prognostic and diagnostic biomarkers after LVAD support and have confirmed their validity in clinical datasets. The area under the curve of the four main hub genes was more than 0.85, indicating high diagnostic ability and good prognosis for patients with DCM with LVAD implantation. However, a significant effect of CCL2, CXCL12, FKBP5, and BMP2 expression was not observed on the left ventricular end-diastolic diameter (LVEDD), left ventricular ejection fraction (LVEF), cardiac index (CI), or support time of LVAD. Conclusion CCL2, CXCL12, FKBP5, and BMP2 could be potential gene biomarkers for patients with DCM after LVAD support. These findings provide critical clues for the therapeutic management of patients with DCM and LVADs. LVEDD, LVEF, CI, and support time of LVAD were not correlated with the expression of these hub genes.